Two Hundred Years of Local Avian Extinctions in Eastern Amazonia. Issue 5 (29th April 2014) - MOURA, NÁRGILA G.; LEES, ALEXANDER C.; ALEIXO, ALEXANDRE; BARLOW, JOS; DANTAS, SIDNEI M.; FERREIRA, JOICE; LIMA, MARIA DE FÁTIMA C.; GARDNER, TOBY A.
Abstract Local, regional, and global extinctions caused by habitat loss, degradation, and fragmentation have been widely reported for the tropics. The patterns and drivers of this loss of species are now increasingly well known in Amazonia, but there remains a significant gap in understanding of long‐term trends in species persistence and extinction in anthropogenic landscapes. Such a historical perspective is critical for understanding the status and trends of extant biodiversity as well as for identifying priorities to halt further losses. Using extensive historical data sets of specimen records and results of contemporary surveys, we searched for evidence of local extinctions of a terra firma rainforest avifauna over 200 years in a 2500 km2 eastern Amazonian region around the Brazilian city of Belém. This region has the longest history of ornithological fieldwork in the entire Amazon basin and lies in the highly threatened Belém Centre of Endemism. We also compared our historically inferred extinction events with extensive data on species occurrences in a sample of catchments in a nearby municipality (Paragominas) that encompass a gradient of past forest loss. We found evidence for the possible extinction of 47 species (14% of the regional species pool) that were unreported from 1980 to 2013 (80% last recorded between 1900 and 1980). Seventeen species appear on the International Union for Conservation of Nature Red List, and many of these are large‐bodied. The species lost from the region immediately around Belém are similar to those which are currently restricted to well‐forested catchments in Paragominas. Although we anticipate the future rediscovery or recolonization of some species inferred to be extinct by our calculations, we also expect that there are likely to be additional local extinctions, not reported here, given the ongoing loss and degradation of remaining areas of native vegetation across eastern Amazonia. Doscientos Años de Extinciones Locales de Aves en la Amazonia Oriental